How leader-follower relations influence nurses' intention to stay: An investigation in a Thai sample - Chuchai Smithikrai (2019)
© 2019 Academic Research Publishing Group. The purpose of this study was to investigate how leader-follower relations may affect nurses' intention to stay by proposing and testing a serial mediation model. Using anonymous questionnaire survey, the sample consisted of 403 registered nurses from private hospitals in Thailand. The PROCESS macro (Model 6) was used to test the hypotheses regarding the serial mediating effects. As predicted, the results indicate that leader-follower relations have both direct and indirect effects on nurses' intention to stay. Moreover, the relationship between leader-follower relations and intention to stay is serially mediated by psychological empowerment, work-life balance, and career satisfaction. It was concluded that the presence of high-quality leader-follower relations create a supportive work context in which nurses are more psychologically empowered, experience greater work-life balance, feel more satisfied with their career, and are more likely to stay at their job.